ASSESSMENT OF LONG-TERM URATE-LOWERING THERAPY EFFECTIVENESS AND ADHERENCE IN PATIENTS WITH GOUT (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the effectiveness of long-term urate-lowering therapy (ULT) and the problems of adherence in patients with gout. The current clinical and social significance of gout, as well as its association with cardiovascular and renal complications, is highlighted. Based on the analysis of scientific literature, the key role of ULT in maintaining serum uric acid (SUA) levels within target ranges is demonstrated. The article discusses patients’ adherence to urate-lowering therapy, reasons for low adherence, and its impact on clinical outcomes. Additionally, methods for assessing adherence, including subjective and objective approaches, the importance of laboratory monitoring, and comprehensive patient education strategies, are reviewed. In conclusion, improving adherence to urate-lowering therapy is crucial for effective gout management, reducing complications, and enhancing patients’ quality of life.
Keywords: Gout, urate-lowering therapy, serum uric acid, treatment adherence, urate-lowering drugs, long-term therapy, complications.